2015
DOI: 10.4102/safp.v57i5.4237
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the prevalence and causes of anaemia in hospitalised elderly patients

Abstract: Introduction: Anaemia is common in the elderly. Little is known regarding anaemia in hospitalised elderly patients in South Africa. A retrospective study determined the prevalence and causes of anaemia in elderly patients hospitalised for acute medical problems.Methods: Patients with anaemia were identified from the computerised database of a geriatric unit. Laboratory tests and clinical information on these patients were reviewed to determine the cause of the anaemia defined according to the WHO criteria (hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…27 The lower prevalence of anaemia reported in the index study as compared to Melku et al study in Ethiopia may be explained by high proportion of vegans among their respondents. 20 Since, anaemia worsens with advancing age, [5][6][7][8][9][10] the higher prevalence of anaemia reported among respondents in France could be due to the high age cutoff of 65 years as compared 60 years used in this study. 27 However, a lower prevalence of 21.1% was reported by Bach et al in a large cohort study in European University Hospitals.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…27 The lower prevalence of anaemia reported in the index study as compared to Melku et al study in Ethiopia may be explained by high proportion of vegans among their respondents. 20 Since, anaemia worsens with advancing age, [5][6][7][8][9][10] the higher prevalence of anaemia reported among respondents in France could be due to the high age cutoff of 65 years as compared 60 years used in this study. 27 However, a lower prevalence of 21.1% was reported by Bach et al in a large cohort study in European University Hospitals.…”
Section: Discussionmentioning
confidence: 81%
“…Various studies also revealed a similar finding. [1][2][3][5][6][7][8][9][10][31][32][33][34] As people age, their erythroid precursors in their bone marrow diminish, and they become less receptive to stimulatory growth factors. 32 Additional reasons found in this study include; swallowing difficulties, a low-protein diet, insufficient fluid intake, loss of appetite, and a negative self-perception of one's nutritional state as one ages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations